The Utility of Xenon-133 Liver Scan in the Diagnosis and Management of Nonalcoholic Fatty Liver Disease - Said A Al-Busafi; Peter Ghali; Philip Wong; Javier A Novales-Diaz; Marc Deschênes (Canadian Journal of Gastroenterology)
Nonalcoholic fatty liver disease (NAFLD) encompasses a wide spectrum of liver damage and is the most common cause of chronic liver diseases in Western countries. Although a relatively common condition affecting approximately 20% of the general population, NAFLD is especially prevalent in obese individuals, a figure likely to rise as obesity rates in Western countries continue to increase. Liver biopsy remains the gold standard diagnostic method; however, its invasive nature, among other factors, has prompted the need to develop less invasive, alternative methods to quantify hepatic fat and determine disease severity. Xenon-133 liver scanning is one such method that has been in use for more than 10 years in the evaluation of patients with suspected NAFLD. This study compared Xenon-133 liver scan with other currently used, invasive and noninvasive methods of liver assessment.